Virtue Ethics, Situationism, and the Filipino Business Leader’s Compassion for the Poor - Cleofas, Jacklyn A (Archīum Ateneo, 2016)
Catholic social teaching prominently features virtue. For instance, the Vocation of the Business Leader tells us that the virtues of compassion and responsibility toward the poor are necessary for living out the Gospel. Consequently any challenge against virtue ethics has implications for Catholic social teaching. A recent debate among philosophers working in moral psychology features one such challenge from philosophical situationists. Situationists believe that evidence from social psychology demonstrates that virtue is neither robust nor reliable in producing morally desirable behavior. In this paper I discuss the situationist challenge against virtue vis-a-vis a difficulty among Filipino business leaders to behave compassionately toward the poor. I argue that this difficulty about compassion stems in part from a tendency to put primacy on character-based explanations for both poverty and prosperity